2017
DOI: 10.1097/psy.0000000000000477
|View full text |Cite
|
Sign up to set email alerts
|

Mean Levels and Variability in Affect, Diabetes Self-Care Behaviors, and Continuously Monitored Glucose: A Daily Study of Latinos With Type 2 Diabetes

Abstract: Objective This study investigated between-person and within-person associations among mean levels and variability in affect, diabetes self-care behaviors, and continuously monitored glucose in Latinos with type 2 diabetes. Methods Fifty participants (mean age=57.8 [SD=11.7] years, 74% women, mean A1c=8.3% [SD=1.5%]) wore a “blinded” continuous glucose monitor for 7 days, and they responded to twice-daily automated phone surveys regarding positive affect (PA), negative affect (NA) and self-care behaviors. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 37 publications
2
44
2
Order By: Relevance
“…Overall, the results of this systematic review do not provide clear evidence for a link between intraday GV and mood states in adults with diabetes 19,20,24,25 . A significant association was found between a higher rate of postprandial glucose increase and more negative mood symptoms in persons with type 2 diabetes, 22,23 warranting further research.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Overall, the results of this systematic review do not provide clear evidence for a link between intraday GV and mood states in adults with diabetes 19,20,24,25 . A significant association was found between a higher rate of postprandial glucose increase and more negative mood symptoms in persons with type 2 diabetes, 22,23 warranting further research.…”
Section: Discussioncontrasting
confidence: 56%
“…Five studies were conducted in North America 20,22‐25 and three in Europe 18,19,21 . Research designs were observational (n = 5), 18,19,24‐26 crossover randomized controlled trials (n = 2) 21,22 and experimental (n = 1) 20 . Details of the study design and participant characteristics are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations